Participação da apolipoproteína-E na atividade microbicida “in vitro” contra o Mycobacterium tuberculosis - Rossi, Kaymerê Bispo (2014)
Lipids compose about 60% of the Mycobacterium tuberculosis (Mtb) cell wall, preventing the passage of a large amount of substances and plays an important role in its immunopathogenesis. CD1 molecules present these antigens to lymphocytes Apolipoprotein E (ApoE) is a glycoprotein with wide tissue distribution, which facilitates the presentation of lipids by CD1. ApoE has three major protein isoforms: ApoE2, ApoE3 and ApoE4, which have different structure and function. Some isoforms are associated to some infectious diseases, such as labial herpes, severe liver damage caused by hepatitis C, children diarrhea and lung tuberculosis. At this context, we evaluated the involvement of ApoE in microbicidal activity in vitro against Mtb. Hence, 34 volunteers were invited to participate in our study, 13 TST-, 17 TST+ and 4 individuals with active pulmonary tuberculosis. The use of ApoE depleted human plasma at the in vitro microbicidal activity assays showed a significant increase (p=0,02) in the numbers of mycobacteria (431.5 ± 81.92 UFC) when compared to the control group (313.0 ± 74.61 UFC). Those results were confirmed by an experimental model using splenocytes from C57BL/6 mice (815.9 ± 76.32 UFC) and APOE knockout animals (1133 ± 86.85 UFC) (p = 0.021). In addition, cells from TST positive individuals produced significantly lower IL-10 when infected by Mtb in the presence of ApoE depleted human plasma (866.7 ± 447.8 pg/ml) than in the presence of untreated plasma (1089 ± 481.3) (p=0,023). Our data suggest that ApoE have a remarkable role in the activation of immune response and its absence can impair immunity to tuberculosis